Doctoral preparation of scientifically based educational researchers - Eisenhart, Margaret; DeHaan, Robert L. (Educational Researcher, 2005)
Finding improved ways to train education researchers has taken on new urgency as federal legislation such as the No Child Left Behind Act of 2001 and the Education Sciences Reform Act of 2002 call for
Keywords: culture scientifique; neurosciences; utilisation des recherches